2015
DOI: 10.1042/bj20150851
|View full text |Cite
|
Sign up to set email alerts
|

The activating role of phospho-(Tyr)-calmodulin on the epidermal growth factor receptor

Abstract: The activity of calmodulin (CaM) is modulated not only by oscillations in the cytosolic concentration of free Ca 2 + , but also by its phosphorylation status. In the present study, the role of tyrosine-phosphorylated CaM [P-(Tyr)-CaM] on the regulation of the epidermal growth factor receptor (EGFR) has been examined using in vitro assay systems. We show that phosphorylation of CaM by rat liver solubilized EGFR leads to a dramatic increase in the subsequent phosphorylation of poly-L-(Glu:Tyr) (PGT) by the recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 59 publications
(91 reference statements)
2
21
0
Order By: Relevance
“…As CaM is also a good substrate for the EGFR [17], it was expected that phospho-Tyr-CaM could also interact with the receptor. This indeed was the case [18,19], and the site of interaction of phospho-Tyr-CaM with the receptor was stablished to be the same that the one for non-phosphorylated CaM located at the cytosolic juxtamembrane region encompassing the sequence 645 RRRHIVRKRTLRRLLQ 660 [19]. The NMR-derived structure of a peptide corresponding to the transmembrane (TM) and the cytosolic juxtamembrane (JM cyt ) segment, where the CaM-BD is located, reconstituted in lipid bicelles shows that they form dimers and that the CaM-BD presents two helical segments divided by a flexible linker [20,21] (see Figure 2).…”
Section: Phospho-tyr-cam In Pathophysiologymentioning
confidence: 71%
See 2 more Smart Citations
“…As CaM is also a good substrate for the EGFR [17], it was expected that phospho-Tyr-CaM could also interact with the receptor. This indeed was the case [18,19], and the site of interaction of phospho-Tyr-CaM with the receptor was stablished to be the same that the one for non-phosphorylated CaM located at the cytosolic juxtamembrane region encompassing the sequence 645 RRRHIVRKRTLRRLLQ 660 [19]. The NMR-derived structure of a peptide corresponding to the transmembrane (TM) and the cytosolic juxtamembrane (JM cyt ) segment, where the CaM-BD is located, reconstituted in lipid bicelles shows that they form dimers and that the CaM-BD presents two helical segments divided by a flexible linker [20,21] (see Figure 2).…”
Section: Phospho-tyr-cam In Pathophysiologymentioning
confidence: 71%
“…evidenceBiological effect (Ref. )Functional and pathological implicationsp-Y-CaMDGNG Y 99 ISAAAffect EF-hand IIIEGFR in vitro Phospho-Y-CaM enhances ligand-dependent EGFR activation [19]. CancerGQVN Y 138 EEFVAffect EF-hand IVc-Src In vivo The pleiotrophin/PTPRZ1 pathway enhances CaM phosphorylation in SCLC [37].…”
Section: Phospho-tyr-cam In Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the phosphorylated CaM can bind at the same site as the non-phosphorylated site. It has already been observed that phosphorylated and non-phosphorylated CaM share the same binding site ( 645 RRRHIVRKRTLRRLLQ 660 ) at the cytosolic juxtamembrane region of the EGFR [72]. …”
Section: Modeling the Phosphorylated Cam Interaction And Ternary Complexmentioning
confidence: 99%
“…Ca 2+ -CALM binding to the CALM binding domain (CALM-BD) of cytosolic juxtamembrane region of the receptor plays an important trigger role in ligand-dependent activation EGFR in living cells [42][43][44]. A further study was shown that nonphosphorylated CaM only interacts with the EGFR when is not phosphorylated at Tyr 1173 (tyrosine 1173 ) [45].Herein, We found here for the rst time that treatment with knock-out of CALM1 and EGFR inhibitors have signi cant effects against tumors in vivo and in vitro in ESCC. Recent studies have pointed to the potential for combinations of EGFR inhibitors with TKIs to overcome a certain degree of resistance for EGFR mutations [46].…”
Section: Discussionmentioning
confidence: 99%